Tom Clancy : red winter - Cameron, Marc (New York : Berkley, 2023)
"1985, Nevada. A top-secret military stealth plane crashes in the mountains. An East German agent makes off with a critical piece of technology from the crash site. East Berlin. A mysterious figure contacts the CIA with an irresistible offer -- invaluable information on the communist nation's espionage exploits. Someone will have to go behind the Iron Curtain to determine whether this is one of the agency's greatest coups or a deadly trap. Deputy Director James Greer knows the perfect man for this job--a young analyst named Jack Ryan."--Back cover.
Keywords: Ryan, Jack, -- Sr. (Fictitious character) -- Fiction; United States. -- Central Intelligence Agency -- Fiction; Intelligence officers -- United States -- Fiction; Defectors -- Fiction; Cold War -- Fiction; Thrillers (Fiction); Action and adventure fiction; Spy fiction